Coccolithophorids in Polar Waters: Wigwamma spp. Revisited - Thomsen, Helge A.; Østergaard, Jette B.; HELDAL, Mikal (Acta Protozoologica, 2015)
A contingent of weakly calcified coccolithophorid genera and species were described from polar regions almost 40 years ago. In the interim period a few additional findings have been reported enlarging the realm of some of the species. The genus Wigwamma is revisited here with the purpose of providing, based on additional sampling from both polar regions, an update on species morphology, life history events and biogeography that can serve as a reference for the future. A new genus, Pseudowigwamma gen. nov. is described to accommodate Wigwamma scenozonion, a species which critically deviates from a core group of five Wigwamma species in terms of coccolith morphology and life history events. Wigwamma armatura sp. nov. is described on the basis of material from the Weddell Sea, Antarctica. While fitting nicely into the Wigwamma generic concept, the species adds new dimensions to the overall appearance of the coccolith armour of the cell.